Complete Excision of a Simple Dacryops Using Fibrin Sealant and Trypan Blue Mixture. Issue 1 (January 2019) - Men, Clara J.; Yang, Patrick; Gur, Zvi; Paik, Ji-Sun; Kikkawa, Don O.; Korn, Bobby S.
Abstract : A 69-year-old woman presented to the oculofacial plastic service with a painless superotemporal subconjunctival mass in the OS. Over the past year, the lesion had been progressively enlarging, resulting in horizontal diplopia with lateral gaze. Visual acuity was within normal limits with no evidence of optic neuropathy. On examination, the lesion was tense, transilluminated, and was clinically consistent with a simple dacryops. Complete excision of the lesion was planned under local anesthesia with monitored care. To facilitate complete removal of the lesion, fibrinogen and a mixture of thrombin and trypan blue were injected to fill the cyst cavity. This blue-stained fibrin clot allowed for easy visualization of the border and ensured complete excision without collateral damage to surrounding normal tissue. Simple dacryops is often difficult to remove completely with its capsule intact and this technique allows for clear delineation of the cyst and preservation of epithelial integrity for complete and efficient removal. Abstract : A case report of a 69-year-old woman with a superotemporal orbital mass consistent with a simple dacryops, with complete excision performed using fibrin sealant mixed with trypan blue.